Analysis of the Spanish Version of the Chinese Text of the "Platform Sutra" - Cao, Xuanzi; Franquesa, Montserrat (CLINA Revista Interdisciplinaria de Traducción Interpretación y Comunicación Intercultural, 2020)
The Altar-Sutra, a reference book in Buddhism attributed to Hui Neng (638-713) which is more than a thousand years old, was first translated into English in 1933 by Wong Mou-Lam. The oldest manuscript was discovered in 1900 in Dun Huang by the English archaeologist Auren Stein. The first Spanish version was by Laureano Ramírez Bellerín (Hui 2000). Taking into account the lack of Buddhist terms in Spanish and the difficulties associated to transcribing Sanskrit, the translation techniques adopted and the intervention of the translator deserve a rigorous analysis. In a broader aspect, the comparative analysis presented in this article is not unrelated to the context of globalization. The study of cross-cultural contact and reciprocal influences has become necessary to understand the world in which we live.